1997
DOI: 10.1007/s001340050474
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care 1980–1995: change in patient characteristics, nursing workload and outcome

Abstract: Objective: To assess temporal changes in patient characteristics, nursing workload and outcome of the patients and to compare the actual amount of available nursing staff with the estimated needs in a medical-surgical ICU. Design: Retrospective analysis of prospectively collected data. Setting: A medical-surgical adult intensive care unit (ICU) in a Swiss university hospital. Patients: Data of all patients staying in the ICU between January 1980 and December 1995 were included. Interventions: None. Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
16

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 20 publications
3
48
0
16
Order By: Relevance
“…A study carried out in Switzerland confirmed this premise in a comparative analysis of 35.327 ICU patients' characteristics, hospitalized between 1980 and 1995, showing a significant increase in patients' age during that period (1) .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A study carried out in Switzerland confirmed this premise in a comparative analysis of 35.327 ICU patients' characteristics, hospitalized between 1980 and 1995, showing a significant increase in patients' age during that period (1) .…”
Section: Discussionmentioning
confidence: 73%
“…Researches appoint that specialized nursing workforce is one of the main sources of resource consumption in these environments, explaining the need for adequate staff dimensioning (1)(2)(3)(4) . In this context, one of the challenges ICU managers face is to adapt the nursing staff to the care demands of severe patients, which includes an increasingly large contingent of elderly and elder elderly patients, due to global population aging.…”
Section: Introductionmentioning
confidence: 99%
“…These stressful conditions are universal and researchers in various parts of the world, e.g. Australia (Tarnow-Mordi et al, 2000), Belgium (Stordeur et al, 2001), Great Britain (McGowan, 2001Payne, 2001), Greece (Alexopoulos et al, 2003), Ireland (Wynne et al, 1993), Switzerland (Jakob and Rothen, 1997), Taiwan (Lee and Wang, 2002) and in the US (Santos et al, 2003) have shown that nurses have to cope with a strenuous workload and occupational stress. There are no published studies of stress and workload among Icelandic nurses, who are the subjects of this study, so it is important to find out if they experience occupational stress in ways similar to nurses in other countries.…”
Section: Occupational Stress Among Icelandic Nursesmentioning
confidence: 99%
“…Nas UTI(s), reconhecidas pela elevada carga, (que representa um fator de alto custo), e pelo elevado índice de mortalidade, (medida que expressa produção/rendimento) (3) , durante décadas utilizou-se a razão mortalidade/morbidade como parâmetro de escolha para descrever resultado da eficiência do cuidado intensivo. Todavia, nos últimos anos, a inclusão da demanda de trabalho de enfermagem como um parâmetro para avaliação dos resultados, tem sido também considerada, devido ao seu impacto na qualidade da assistência intensiva (3) .…”
Section: Introductionunclassified